2018
DOI: 10.18295/squmj.2018.18.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Glycated Haemoglobin and Carotid Atherosclerotic Disease Among Patients with Acute Ischaemic Stroke

Abstract: Objectives: This study aimed to determine the relationship between glycaemic control and carotid atherosclerotic disease among patients with acute ischaemic stroke (AIS). Methods: This retrospective cross-sectional study took place in the Neurology Department of King Fahad Hospital of University, Khobar, Saudi Arabia, from April to October 2017. Data were collected from the medical records of 244 patients with a diagnosis of AIS confirmed by computed tomography. Doppler ultrasounds of the carotid artery were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…A regression analysis indicated that dyslipidaemia and age were independently correlated with high CIMT, but not with HbA1c levels. 21 The results of this study are similar to those of other studies exploring the role of carotid ultrasound CIMT and plaque findings as surrogate risk factors for stroke in general, as well as among patients with diabetes. 20,22,23 However, the strength of the relationship between CIMT and stroke among diabetic patients has not yet been determined.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…A regression analysis indicated that dyslipidaemia and age were independently correlated with high CIMT, but not with HbA1c levels. 21 The results of this study are similar to those of other studies exploring the role of carotid ultrasound CIMT and plaque findings as surrogate risk factors for stroke in general, as well as among patients with diabetes. 20,22,23 However, the strength of the relationship between CIMT and stroke among diabetic patients has not yet been determined.…”
supporting
confidence: 88%
“…19,20 In this issue of SQUMJ, Nazish et al have published a retrospective study in which they report a relationship between glycated haemoglobin (HbA1c) and CIMT and carotid plaques among adult ischaemic stroke patients who underwent carotid Doppler ultrasonography in addition to brain imaging. 21 The authors found a significant association between mean HbA1c levels and increased CIMT, but not with the presence of carotid plaques. A regression analysis indicated that dyslipidaemia and age were independently correlated with high CIMT, but not with HbA1c levels.…”
mentioning
confidence: 90%
“…Various studies have demonstrated that diabetes mellitus, smoking, and hypertension, consider the main risk factors of atherosclerosis, which are correlated with an increased production of ROS by the endothelium [21] [22] [23]. It has been recently found a good correlation between elevated HbA1c values and the atherosclerosis [24] [25] [26] which result from oxidative stress induced by various glucose oxidation, change in antioxidant enzymes status and impaired glutathione metabolism [27] [28].…”
Section: Discussionmentioning
confidence: 99%
“…Haemoglobin absorbs light in the near-infrared (NIR) wavelength, specifically at wavelengths from 740-760 nm [10]. Intravenous blood contains deoxyhaemoglobin at a concentration greater than that of haemoglobin: the concentration of haemoglobin in veins is approximately 47%, whereas the concentration of haemoglobin in arteries is 90-95% [11]. The two types of haemoglobin have different light absorption properties, as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%